Accuracy of screw stabilization of the dorsal pelvic ring using a hybrid operating room: 5 Year experience in a level 1 trauma center. Issue 10 (October 2021) - Richter, P.H.; Blidon, A.; Eickhoff, A.; Gebhard, F.; Schuetze, K.
Highlights: Intraoperative navigation in a hybrid OR ensures a high accuracy for SI screws. Due to the large field of view and high image quality TSTI screws can be safely implanted in S1 and S2. Utilization of a hybrid-OR is accompanied with a steep learning curve. A reduction of screw perforations and cut to suture time with advancing years could be seen, but was not statistically significant. Abstract: Introduction: Accuracy for screw placement in the dorsal pelvic ring can be enhanced using intraoperative 3D navigation. Advances in intraoperative imaging lead to benefits for pelvic surgery. New c-arms are equipped with flat panel detectors, which have a larger detector and assure higher image quality with accompanying dose reduction. A hybrid OR is defined by a fixed imaging system in an operating room providing the benefit of the surgical environment in combination with advanced intraoperative imaging. Aim of our investigation was to analyze the accuracy of navigated sacroiliac (SI) and transsacral transiliac (TSTI) screws in the dorsal pelvic ring, which were implanted with a hybrid OR in the first five years of use. Material and methods: All percutaneous SI or TSTI screws implanted in the hybrid OR using intraoperative navigation in the first 5 years of utilization (between June 2012 to June 2017) were included. Intraoperative 3D-scans and postoperative computed tomography were examined for screw perforation. Results: 210 SI and TSTI screws were implanted in 187 patients using intraoperative navigation in the hybrid-OR. 90.6 % of SI screws showed no cortical perforation. 6, 3 % had a grade 1, 2.4 % a grade 2 and 0.8 % a grade 3 perforation. In 80.7 % of TSTI screws no perforation and in 13.3 % a grade 1 perforation was detected. 3.6 % showed a grade 2 and 2.4 % a grade 3 perforation. No significant difference between both screw types regarding the grade of cortical perforation could be seen. No significant relation between perforation rate and year of operation could be detected. Conclusion: Intraoperative navigation in a hybrid OR ensures a high accuracy for SI screws. Due to the large field of view and high image quality TSTI screws can be safely implanted in S1 and S2. Utilization of a hybrid-OR is accompanied with a steep learning curve.